Automated information-diagnostic system operational assessment of the degree of fuel injectors zakoksuvannya gas turbine engines - Кулик, М.С.; Чоха, Ю.М.; Чумак, О.І.; Федорчук, О.П. (Proceedings of National Aviation University, 2006)
Offered technology to realization of the expert system diagnostic modern gas turbine engines for the current operative determination degree contamination worker fuel injector without their unmounting with GTE.